2018
DOI: 10.1063/1.5037116
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence quantum yields for atomically thin-layered ReS2: Identification of indirect-bandgap semiconductors

Abstract: Rhenium dichalcogenides have attracted considerable attention as new members of group VII layered semiconductor transition-metal dichalcogenides (TMDs) with respect to fundamental physics and potential applications. In this study, room-temperature photoluminescence (PL) spectra, as well as PL quantum yields (QYs) of thin-layer rhenium disulfide (ReS2), were evaluated. Low PL QYs of ∼10–4 were determined from a monolayer thickness to seven layers (1–7L) of ReS2 regardless of the layer number. These low PL QYs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 44 publications
5
32
0
Order By: Relevance
“…However, an indirect bandgap of 1.47 eV has been reported 30 . Low photoluminescence (PL) quantum yield generally observed in all thickness appear to suggest that ReS 2 is indirect semiconductor 31 , while k-space photoemission microscopy revealed a direct bandgap in the bilayer (2L) ReS 2 32 . On the second issue, early experimental and first-principle studies have suggested that the interlayer coupling in ReS 2 is much weaker than other TMDs 5 .…”
Section: Introductionmentioning
confidence: 95%
“…However, an indirect bandgap of 1.47 eV has been reported 30 . Low photoluminescence (PL) quantum yield generally observed in all thickness appear to suggest that ReS 2 is indirect semiconductor 31 , while k-space photoemission microscopy revealed a direct bandgap in the bilayer (2L) ReS 2 32 . On the second issue, early experimental and first-principle studies have suggested that the interlayer coupling in ReS 2 is much weaker than other TMDs 5 .…”
Section: Introductionmentioning
confidence: 95%
“…The subsequent experimental studies, however, strongly oppose these predictions about the structural and electronic properties, revealing strong layer-dependent optical [11,27] and vibrational [28] properties of ReS 2 . An additional indication of lesser quantum yields of photoluminescence (PL) with lowering thicknesses [29] also contradicts the direct band gap nature of monolayer and few-layered ReS 2 . The optical response divulges that, starting from the monolayer up to seven layers, ReS 2 remains an indirect band gap semiconductor [28].…”
Section: Introductionmentioning
confidence: 99%
“…The PL intensity and absorption data of the reference sample are then measured using microscopes for comparison with data obtained from the 1L-TMD samples using the same experimental conditions [27][28][29][30]. In this method, the reference samples are usually thin films made of fluorescent organic dyes, such as 3-borylbithiophene derivatives [27][28][29][30] or rhodamine 6G (R6G) [1,13,14]. The thicknesses and emission profiles of the reference films must be spatially uniform at micro-scale dimensions to permit comparison with the local PL of micro-sized 1L-TMDs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are undesirable for use as reference samples. Previously, 3-borylbithiophene derivatives have been used as reference films [28][29][30]; however, controlling the uniform dispersion of organic molecules in a matrix is technically difficult. Therefore, for the reliable measurement of the QY of 1L-TMDs, the method of preparing thin films containing uniformly dispersed organic dyes is still in high demand.…”
Section: Introductionmentioning
confidence: 99%